Antiglycation and Antioxidant Activity from Methanol Extract and Fraction of Xylocarpus granatum Stem - Intan Noviarni; Irmanida Batubara; Sastia Prama Putri (Jurnal Kimia Sains dan Aplikasi, 2020)
The objective of this research was to determine the antioxidant and antiglycation activity of methanol crude extract of Xylocarpus granatum stem and its fraction. The methanol crude extract was fractioned by liquid-liquid extraction to obtain three fractions, which were n-hexane fraction, ethyl acetate fraction, and methanol fraction. Antioxidant activity was performed using scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH). The antiaging activity was identified based on the ability to inhibit the formation of advanced glycation end products (AGEs). The results of the study showed that methanol crude extract and all fractions had an antioxidant and antiglycation activity that significantly different from each other (P<0.05). The results show that the most active antiglycation and antioxidant activity was the methanol fraction with IC50 were 71.55 ppm and 8.52 ppm, respectively. The methanol fraction contained an alkaloid, flavonoid, phenolic, and triterpenoid compounds. Subsequent fractionation of the methanol fraction guided by bioassay showed that sub-fraction 1 had the best antiglycation and antioxidant activity. Based on the color of the chromatogram obtained at UV 366 nm, the chemical component contained in the most active fraction was the flavonoid group.